Reformation and/or Union - Nagy, Levente (Bogoslovni vestnik, 2024)
The study presents some phenomena of the impact of the Reformation on Eastern Orthodoxy. In the 17th century, Eastern Orthodoxy was assailed with offers of union from both Protestants and Catholics. The Greek-Eastern Church responded to these challenges with some reforms. So, like the Protestant Reformation and the Catholic revival, we can speak of a Reformation, and revival in the Greek Orthodox Church as well. This Orthodox reform manifested itself primarily within the Patriarchate of Constantinople, and within the Romanians of the Principality of Transylvania. In our study, we present the activity of some Greek Philo-Calvinist intellectuals (Nikodemos Metaxas, Zacharia Gerganos, Metrophanes Kritopoulos). At the centre of this presentation is the Calvinist catechism of Patriarch Cyril Lucaris. We analyse the existing links between Lucaris and between the teachers and preachers of the Calvinist college in Alba Iulia (Johann Heinrich Alsted, Johann Heinrich Bisterfeld, György Csulai, István Katona Geleji). We provide new data about the translators of the New Testament of Bălgrad (1648), which is the first complete edition of the New Testament in Romanian. We present the Calvinist features of thistranslation, as well asthe fact that in the preface of the New Testament of Bălgrad,some ideas are taken from the writings of Francis Bacon.
Keywords: catholic revival; Cyril Lucaris; katoliški preporod; Kiril Lukaris; New Testament of Bălgrad (1648); Nova zaveza iz Bălgrada (1648); orthodox revival; pravoslavni preporod; protestant reformation; protestantska reformacija